2021
DOI: 10.1002/hbe2.304
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the emotional response to COVID‐19 information in news and social media: A mental health perspective

Abstract: The impact of the Covid‐19 pandemic and ensuing social restrictions has been profound, affecting the health, livelihoods, and wellbeing of populations worldwide. Studies have shown widespread effects on mental health, with an increase in stress, loneliness, and depression symptoms related to the pandemic. Media plays a critical role in containing and managing crises, by informing society and fostering positive behavior change. Social restrictions have led to a large increase in reliance on online media channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 66 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…Social restrictions during the COVID pandemic have led to an increase in reliance on online social media channels, influencing mental health and well-being [ 37 ]. Importantly, the current study included social networking use as a separate use category, but we did not find any associations between older people’s use of social media and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Social restrictions during the COVID pandemic have led to an increase in reliance on online social media channels, influencing mental health and well-being [ 37 ]. Importantly, the current study included social networking use as a separate use category, but we did not find any associations between older people’s use of social media and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is a COVID-19 news post on Twitter that was perceived as inaccurate and politically loaded by the audience 3 . Published by a popular Nigerian media account (Punch Newspaper) the news post, arguably, instigated a high level of anger in the user responses to the posted news.…”
Section: Discussionmentioning
confidence: 99%
“…M EDIA has played a pivotal role in containing the COVID-19 pandemic through public information [1]. But COVID-19 news often contains distressing contents, e.g., death tolls, which may contribute to negative feelings in the audience [2,3], discouraging them from following the news. Due to the multifaceted nature of this problem, it would be hard to hypothesize that COVID-19 news has been the primary factor in people experiencing certain emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent COVID-19 studies have begun to document the emotional and psychological effects of the pandemic for older adults related to, among other things, loneliness and isolation, familial perceptions of concern, and institutional trust and trust in political leadership [11][12][13][14][15]. To date, however, relatively few studies have examined the relationship between COVID-19 news consumption and wellbeing among adults residing in the US or in other areas of the world [16][17][18][19]. Most research has focused on younger populations, though one recent study found a positive effect of COVID-19 media dependency on anxiety for both women and men [20].…”
Section: Introductionmentioning
confidence: 99%